Climate Change and Rainfall in the Pacaya Samiria National Reserve - Condori Islachin, Rosmery (2024)
Rainfall and temperature are essential inputs for agricultural production, especially climate change- related ones. In turn, it is necessary for the development and survival of both men and animals at all biotic levels. In a reserve of great importance for the country, such as the Pacaya Samiria, these two factors play a preponderant role in the survival of animals and inhabitants ofit. In this paper, VAR analysis with Granger's causality was used to determine the relationship between both variables. It was shown that there was a short-term positive relationship between climate change and rainfall in Pacaya Samiria.